New Public Management (NPM): Pendekatan Baru Manajemen Sektor Publik - Mahmudi Mahmudi (Universitas Islam Indonesia, 2003)
This article discussed about the concept of New Public Management and its im¬pact to the developing countries, i.e. Indonesia. As a global movement, New Public Manage¬ment became the paramount issues in modernizing management of public sector organization around the world. Besides New Public Management, there are several concepts of manageri¬alism in public sector, i.e Reinventing Government, Market-Based Public Administration, and Post-Bureaucratic Paradigm. All that concepts support managerial approach, as oppose to administration approach, in promoting public sector organization. In this article we explore the essence of New Public Management approach, the benefits and risks of NPM, and the problem faced by developing countries in implementing NPM.Keywords: New Public Management, Public Administration, Localized Contingency, Market Centered.